Pemanfaatan tepung kulit pisang raja (Musa paradisiaca) dalam formulasi pakan ikan nila (Oreochromis niloticus) - Nanariain, Rian M.; Lumenta, Cyska; Pangkey, Henneke (e-Journal BUDIDAYA PERAIRAN, 2017)
The objective of this research was to evaluate the effect of supplementation of banana skin (Musa paradisiaca) in feed formulation on absolute growth, relative growth, daily growth and feed efficiency of nile tilapia.  The research was conducted at the Laboratory of Aquaculture Technology, Faculty of Fisheries and Marine Science, Sam Ratulangi University. The research used Complete Randomized Design with five treatments inluded A: without supplementation banana skin powder, B: 40%, C: 30%, D: 20% and E: 10% of banana skin powder. Each treatment  had three replications.  The result showed the best response was observed in treatment D  with absolute growth o43.11 g, relative growth 88.9%, daily growth 10.17%,  and feed efficiency 3.20%. Keywords:  feed formulation, banana skin, nile tilapia, absolute growth, relative growth,   daily growth,  feed efficiency